Improving teaching about medically unexplained symptoms for newly qualified doctors in the UK: findings from a questionnaire survey and expert workshop. Issue 4 (27th April 2017) - Yon, Katherine; Habermann, Stephanie; Rosenthal, Joe; Walters, Kate R; Nettleton, Sarah; Warner, Alex; Lamahewa, Kethakie; Buszewicz, Marta
Abstract : Objectives: Medically unexplained symptoms (MUS) present frequently in healthcare, can be complex and frustrating for clinicians and patients and are often associated with overinvestigation and significant costs. Doctors need to be aware of appropriate management strategies for such patients early in their training. A previous qualitative study with foundation year doctors (junior doctors in their first 2 years postqualification) indicated significant lack of knowledge about this topic and appropriate management strategies. This study reviewed whether, and in what format, UK foundation training programmes for newly qualified doctors include any teaching about MUS and sought recommendations for further development of such training. Design: Mixed-methods design comprising a web-based questionnaire survey and an expert consultation workshop. Setting: Nineteen foundation schools in England, Wales and Northern Ireland Participants: Questionnaire administered via email to 155 foundation training programme directors (FTPDs) attached to the 19 foundation schools, followed by an expert consultation workshop attended by 13 medical educationalists, FTPDs and junior doctors. Results: The 53/155 (34.2%) FTPDs responding to the questionnaire represented 15 of the 19 foundation schools, but only 6/53 (11%) reported any current formal teaching about MUS within their programmes. However, most recognised the importance of providing such teaching, suggesting 2–3 hours per year. All those attending the expert consultation workshop recommended case-based discussions, role-play and the use of videos to illustrate positive and negative examples of doctor–patient interactions as educational methods of choice. Educational sessions should cover the skills needed to provide appropriate explanations for patients' symptoms as well as avoid unnecessary investigations, and providing information about suitable treatment options. Conclusions: There is an urgent need to improve foundation level training about MUS, as current provision is very limited. An interactive approach covering a range of topics is recommended, but must be delivered within a realistic time frame for the curriculum.